Results of phlegmon’s treatment lacrimal sac and dacryocystocele at newborns - M. E. Valjavskaja; A. V. Ovchinnikova; E. Ju. Markova (Oftalʹmologiâ, 2014)
Results of treatment of 113 children (124 eyes) with phlegmon lacrimal sac (78 eyes) and dacryocystocele (46 eyes) are analysed. Features of tactics of maintaining patients with purulent complication phlegmon lacrimal sac newborns (phlegmon) and dacryocystocele, as main reason for its development are described. It is shown that early surgical treatment of these conditions promotes fast recovery, prevention of complications and refusal in most cases from application of the general antibacterial therapy. It is revealed that at dacryocystocele the risk of development phlegmon lacrimal sac is increased.